2013
DOI: 10.2178/jsl.7804030
|View full text |Cite
|
Sign up to set email alerts
|

Computably Isometric Spaces

Abstract: We say that an uncountable metric space is computably categorical if every two computable structures on this space are equivalent up to a computable isometry. We show that Cantor space, the Urysohn space, and every separable Hilbert space are computably categorical, but the space [0, 1] of continuous functions on the unit interval with the supremum metric is not. We also characterize computably categorical subspaces of ℝn, and give a sufficient condition for a space to be computably categorical. Our interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 30 publications
1
71
0
3
Order By: Relevance
“…In particular, Melnikov and Nies showed that computably presentable compact metric spaces are ∆ 0 3 -categorical and that there is a computably presentable Polish space that is not ∆ 0 2 -categorical [26]. At the same time, Melnikov showed that the Cantor space, Urysohn space, and all separable Hilbert spaces are computably categorical (as metric spaces), but that (as a metric space) C[0, 1] is not [24]. Recently, Greenberg, Knight, Melnikov, and Turetsky announced an analog of Goncharov's syntactic characterization of relative computable categoricity for metric spaces [13].…”
Section: 23mentioning
confidence: 99%
“…In particular, Melnikov and Nies showed that computably presentable compact metric spaces are ∆ 0 3 -categorical and that there is a computably presentable Polish space that is not ∆ 0 2 -categorical [26]. At the same time, Melnikov showed that the Cantor space, Urysohn space, and all separable Hilbert spaces are computably categorical (as metric spaces), but that (as a metric space) C[0, 1] is not [24]. Recently, Greenberg, Knight, Melnikov, and Turetsky announced an analog of Goncharov's syntactic characterization of relative computable categoricity for metric spaces [13].…”
Section: 23mentioning
confidence: 99%
“…Ng have investigated computable categoricity questions with regards to the space C[0, 1] of continuous functions on the unit interval with the supremum norm. In particular, they have shown that C[0, 1] is not computably categorical as a metric space nor as a Banach space [9], [10]. The study of computable categoricity for countable structures goes back at least as far as the 1961 work of A.I.…”
Section: 2mentioning
confidence: 99%
“…We continue here the program, recently initiated by Melnikov and Nies (see [9], [8]), of utilizing the tools of computable analysis to investigate the effective structure theory of metric structures, in particular L p spaces where p ≥ 1 is computable. Specifically, we seek to classify the L p spaces that are computably categorical in that they have exactly one computable presentation up to computable isometric isomorphism.…”
Section: Introductionmentioning
confidence: 99%